Caso Dermatológico: Granuloma anular - Carvalho, Sandrina (2015)
Granuloma annulare represents a benign idiopathic inflammatory and self-limiting dermatosis with characteristic clinical and histopathological pattern that justify its designation. It is characterized by annular or arciform erythematous plaques, preferably affecting the extensor surface of upper and lower limbs of younger patients. There are four main variants of granuloma annulare: localized, generalized, subcutaneous and perforating. In childhood, localized and subcutaneous forms are most commonly observed. We describe the case of a seven-year-old girl with localized granuloma annulare.